Building Effective Partnerships to Strengthen Guidance and Counseling Service Management at SMA Negeri 2 Sutera - Pebriani Yusnia Herman; Neviyarni N; Yarmis Syukur (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine in depth the forms, mechanisms, and effectiveness of partnerships established to strengthen the management of Guidance and Counseling (BK) services at SMA Negeri 2 Sutera. This study stems from the increasing diversity of student problems, limited service support facilities, and the lack of solid coordination between internal school stakeholders and external partners. The study employed a qualitative approach with a descriptive design. Data were collected through field observations, in-depth interviews, and document review, involving BK teachers, school principals, homeroom teachers, subject teachers, parents, and partner agencies such as the Community Health Center (Puskesmas), the Police Sector, psychologists, and community leaders. Analysis was conducted using the Miles, Huberman, and Saldana model, which includes the stages of reduction, presentation, and conclusion drawing. The results indicate that BK services are operational but not yet fully integrated into the school management system. Internal and external partnerships have been established, but most remain spontaneous and are not supported by standardized SOPs or MoUs. Nevertheless, these collaborations continue to provide benefits in expanding service access and accelerating the handling of student cases. These findings emphasize the need for more planned, documented, and sustainable partnerships to strengthen BK management in schools.